2005
DOI: 10.1017/s1041610205001973
|View full text |Cite
|
Sign up to set email alerts
|

Dementia after traumatic brain injury

Abstract: Early retrospective studies suggested that individuals with a history of a traumatic brain injury (TBI) had a higher risk for dementia than those without a history of TBI. Two meta-analyses demonstrated that the risk for dementia is higher among men, but not women, with a history of TBI. More recent prospective studies, however, are providing discrepant findings, probably due to important methodological differences. TBI is usually associated with significant neuropsychological deficits, primarily in the domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…Both human postmortem and experimental studies have shown Aβ deposition and tau pathology after TBI [84]. The development of AD-like neuropathological and biochemical changes after severe TBI suggested that TBI may be a risk factor for subsequent development of dementia [85]. Epidemiological studies have provided discrepant findings and the relationship between TBI and dementia remains a topic for further investigation.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…Both human postmortem and experimental studies have shown Aβ deposition and tau pathology after TBI [84]. The development of AD-like neuropathological and biochemical changes after severe TBI suggested that TBI may be a risk factor for subsequent development of dementia [85]. Epidemiological studies have provided discrepant findings and the relationship between TBI and dementia remains a topic for further investigation.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…This topic has been recently reviewed by Jellinger (81), who concluded that both Alzheimer's disease and TBI are associated with abnormalities in amyloid and tau protein deposition, and that several epidemiological studies have suggested either that Alzheimer's disease occurs with increased frequency in individuals with TBI or that the age of onset of the disease is reduced after TBI relative to non-injured controls. It may be that the reduced cognitive reserve associated with TBI facilitates earlier symptom manifestation of dementia in individuals destined to develop Alzheimer's disease (82).…”
Section: Relationship Of Tbi To Psychiatric Disordersmentioning
confidence: 99%
“…37 Regarding rehabilitation, older women fared better than men, had shorter length of rehabilitation stay, and had increased use of home health services. 38 Ms. Meyer stressed that gender differences studies may have variable results because of selection bias, sample size, and injury severity; therefore, scientifically rigorous studies are needed.…”
Section: Developing Technologies For the Wounded Warriormentioning
confidence: 99%